2021
DOI: 10.1039/d0nr08294e
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dynamic sub-populations within grafted chains on the protein binding and colloidal stability of PEGylated nanoparticles

Abstract: Polyethylene glycol grafting has played a central role in preparing the surfaces of nano-probes for biological interaction; to extend blood circulation times and to modulate protein recognition and cellular uptake....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…3 These stealth properties of the EGn protected AuNPs (EGn-AuNPs) are believed to be determined by the length and grafting density of the chains in the surface, and recently, it has been reported that the specific chemical properties of the ligands are the major driving force determining the composition of the protein corona that ultimately will be responsible for the prolongation of the blood circulation time and the immune response of the nanoparticles. 4,5 One of the most important parameters determining the interaction of nanoparticles with proteins is the grafting density of the EGn used to protect the surface and therefore its related chain conformation. 6 To determine de grafting density, many approximations have been reported that include nuclear magnetic resonance spectroscopy, 5,7,8 thermogravimetric analysis, 6 isothermal titration calorimetry, 9 analytical ultracentrifugation and total organic carbon analysis, 10 within others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 These stealth properties of the EGn protected AuNPs (EGn-AuNPs) are believed to be determined by the length and grafting density of the chains in the surface, and recently, it has been reported that the specific chemical properties of the ligands are the major driving force determining the composition of the protein corona that ultimately will be responsible for the prolongation of the blood circulation time and the immune response of the nanoparticles. 4,5 One of the most important parameters determining the interaction of nanoparticles with proteins is the grafting density of the EGn used to protect the surface and therefore its related chain conformation. 6 To determine de grafting density, many approximations have been reported that include nuclear magnetic resonance spectroscopy, 5,7,8 thermogravimetric analysis, 6 isothermal titration calorimetry, 9 analytical ultracentrifugation and total organic carbon analysis, 10 within others.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 One of the most important parameters determining the interaction of nanoparticles with proteins is the grafting density of the EGn used to protect the surface and therefore its related chain conformation. 6 To determine de grafting density, many approximations have been reported that include nuclear magnetic resonance spectroscopy, 5,7,8 thermogravimetric analysis, 6 isothermal titration calorimetry, 9 analytical ultracentrifugation and total organic carbon analysis, 10 within others. The chain conformation of the surface-grafted polymer dictates the interfacial properties, and as described within the Alexanderde-Gennes theory, 11,12 the good solvents make the interactions with the solvent preferred over these with other polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…Given the methoxy end group used, the weak decrease in r 1 with pH for MNP@PEG is likely to arise entirely from the protonation of a fraction of bare oxide. In a recent highresolution 1 H NMR study into PEG graft dynamics of SiO 2 NPs in D 2 O, 37 we showed that: (i) the achievable coverage with the ligand used in the current study, MeO-PEG5000-Si(OMe) 3 , is low at <1.0 chains nm −2 , and (ii) at all PEG coverage sufficient to fully disperse the particles, while the chain ends are in the brush confirmation, a fraction of each chain (monomer units closer to the chain grafting point) collapse onto the particle surface. High-resolution 1 H spectra cannot be obtained for MNPs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For instance, polyethylene glycol (PEG), a highly hydrophilic polymer, has been used to reduce protein adsorption and PC formation, and thus lengthen NP blood circulation, which further affects cellular uptake. 136,139,140 However, a recent study has demonstrated that apolipoproteins, known to give nanomaterials stealth properties by reducing mononuclear phagocyte system uptake, are enriched in the HC of liposomes regardless of PEGylation, and they are preferentially enriched in the SC of the PEGylated liposomes. 141 Given the nonbiodegradable nature of PEG, there has been evidence of PEG accumulation as well as uncontrolled oxidative degradation into toxic products, which has inspired the use of polymers such as polyphosphoesters (PPEs) that do not pose the risk of accumulation.…”
Section: Role Of Nanoparticles In Protein Corona Conformationmentioning
confidence: 99%